Bichromatic force on metastable argon for atom trap trace analysis - Feng, Zhongyi; Ebser, Sven; Ringena, Lisa; Ritterbusch, Florian; Oberthaler, Markus K. (Arxiv, 2017)
For an efficient performance of Atom Trap Trace Analysis, it is important to collimate the particles emitted from an effusive source. Their high velocity limits the interaction time with the cooling laser. Therefore forces beyond the limits of the scattering force are desirable. The bichromatic force is a promising candidate for this purpose which is demonstrated here for the first time on metastable argon-40. The precollimated atoms are detected in one dimension and the acquired Doppler shift is detected by absorption spectroscopy. With the experimentally accessible parameters, it was possible to measure a force three times stronger than the scattering force. Systematic studies on its dependence on Rabi frequency, phase difference and detuning to atomic resonance are comparedto the solution of the optical Bloch equations. We anticipate predictions for a possible application in Atom Trap Trace Analysis of argon-39 and other noble gas experiments, where a high flux of metastable atoms is needed.